Double Targeting of Tumors with Pyrenyl-Modified Dendrimers Encapsulated in an Arene-Ruthenium Metallaprism - Pitto-Barry, Anais; Barry, Nicolas P. E.; Zava, Olivier; Deschenaux, Robert; Dyson, Paul J.; Therrien, Bruno (My University, 2011)
The self-assembly of 2,4,6-tris(pyridin-4-yl)-1,3,5-triazine (tpt) triangular panels with p-cymene-ruthenium building blocks and 5,8-dioxido-1,4-naphthoquinonato (donq) bridges, in the presence of pyrenyl-contg. dendrimers of different generations (P0, P1 and P2), affords the triangular prismatic host-guest compds. [Pn?Ru6(p-cymene)6(tpt)2(donq)3]6+ ([Pn?1]6+). The host-guest nature of these systems, with the pyrenyl moiety being encapsulated in the hydrophobic cavity of the cage and the dendritic functional group pointing outwards, was confirmed by NMR spectroscopy (1H, 2D and DOSY). The host-guest properties of these systems were studied in soln. by NMR and UV/Vis spectroscopic methods, allowing the detn. of their affinity consts. (Ka). Moreover, the ability of these water-sol. host-guest systems to carry the pyrenyl-contg. dendrimers into cancer cells was evaluated on human ovarian cancer cells. The host-guest systems are all more cytotoxic than the empty cage [1][CF3SO3]6 (IC50?4 ?M), with the most active compd., [P0?1][CF3SO3]6, being an order of magnitude more cytotoxic. [on SciFinder(R)]
Keywords: pyrenyl dendrimer encapsulated arene ruthenium dioxido naphthoquinonato metallaprism prepn; antiproliferative activity pyrenyl dendrimer encapsulated areneruthenium dioxido naphthoquinonato metallaprism